Evaluasi Ketepatan Penggunaan Antibiotik pada Pasien Geriatri di RSUP Dr. Soeradji Tirtonegoro Klaten Jawa Tengah Periode Januari-Desember 2014 - Ilmawati, Eldesi Medisa (2016)
Antibiotics are a class of drugs most widely used in the world related to the high incidence of bacterial infection. Infectious diseases are often experienced by geriatric patients because of the geriatric susceptibility to infection is higher than other patients. This study evaluated the use of antibiotics for geriatric patients have a greater risk of experiencing the inappropriateness of the use of antibiotics than children and adults. Geriatric patient population is infected with diarrhea, UTI and sepsis in the Hospital dr. Soeradji Tirtonegoro, Klaten, Central Java during 2014 and obtained 34 samples of 18 patients with diarrhea, 6 patients with UTI, and 10 patients with sepsis. Analysis of therapy include the appropriate indication accuracy, right patient, right drug, and the right sodid (dose, frequency, duration, and route of administration)